Permeable Adsorbing Barriers for groundwater remediation from hexavalent chrome pollution. (17th April 2007) - Di Natale, Michele; Greco, Roberto; Musmarra, Dino
Chrome ions removal from aqueous solutions by adsorption onto an activated carbon (Aquacarb 207EA by Sutcliffe Carbon) and a South African coal char is illustrated. Different chrome concentrations, pH and salinity levels are tested. Experimental data are interpreted by means of a Langmuir approach-based model. Results show that a Permeable Adsorbing Barrier (PAB) made of Aquacarb 207EA can protect a shallow aquifer from topsoil Cr(VI) leaching even during heavy rainfalls and that Cr(VI) is desorbed in dry periods, when clean water crosses the PAB, without any dangerous release in the aquifer.